Isoagglutinin reduction in intravenous immunoglobulin (IgPro10, Privigen) by specific immunoaffinity chromatography reduces its reporting rates of hemolytic reactions: an analysis of spontaneous adverse event reports. Issue 6 (14th May 2020) - Shebl, Amgad; Gabriel, Susie; Van Dinther, Kristy; Hubsch, Alphonse; Lawo, John‐Philip; Hoefferer, Liane; Welsh, Susan
Abstract : BACKGROUND: Hemolysis is an infrequent but recognized and potentially serious adverse effect of intravenous immunoglobulin (IVIG). Relatively elevated hemolysis reporting rates were seen with some IVIG products with high anti‐A/B isoagglutinin content, among which IgPro10 (Privigen, CSL Behring). For IgPro10, two isoagglutinin reduction measures were successively implemented: 1) anti‐A donor screening and 2) immunoaffinity chromatography (IAC; Ig IsoLo)–based isoagglutinin reduction step included in the production process. The aim of this analysis was to investigate the effects of these isoagglutinin reduction measures on the reporting rates of IgPro10 hemolysis worldwide. STUDY DESIGN AND METHODS: Between February 2008 and December 2018, hemolysis reports from the CSL Behring Global Safety Database were analyzed in relationship to changes in IVIG IgPro10 production methods. Further analysis classified hemolysis reports by indication and blood group. RESULTS: Median (minimum‐maximum) anti‐A/anti‐B titers were 32 (8‐64)/16 (8‐32) at baseline, 32 (8‐64)/16 (8‐32) after donor screening, and 8 (8‐32)/4 (2‐8) after implementation of IAC. The reporting rate of hemolytic reactions per 1000 kg IgPro10 sold was 4.05 cases at baseline, 2.00 after donor screening, and 0.50 after implementation of IAC. In 2018, there were seven reports of hemolytic reactions; representing 0.18 cases per 1000 kg IgPro10 sold, with a reduction of 95.6% versus baseline. CONCLUSION: Following implementation of the IAC isoagglutinin reduction step, spontaneous reports of hemolytic events with IgPro10 were significantly and consistently reduced versus IgPro10 without isoagglutinin reduction, offering patients a more favorable benefit‐risk profile.